The Relationship Between the Duration of Prolanis Participation and Triglyceride Levels in Patients with Type 2 Diabetes Mellitus at Klinik Griya Sehat - Debora Natasya Yusup; Tasrif Ahmad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Type 2 Diabetes Mellitus (T2DM) is a long-term condition marked by high blood sugar levels resulting from poor insulin operation, which can cause serious blood vessel issues like high triglyceride levels. The government created the Chronic Disease Management Program (PROLANIS) to encourage healthy lifestyles and enhance the quality of life for patients. The time spent participating is vital since the formation of habits usually takes about three months. The study was ethically approved under number KEPK/UMP/193/VI/2025. An observational analytic design with a cross-sectional approach was employed. Samples were selected using purposive sampling. Primary data were obtained from triglyceride measurements, while secondary data regarding participation duration were retrieved from medical records. The results showed a correlation coefficient of -0.026 with p = 0.897 (sig.>= 0.05). The direction of the relationship suggests that longer PROLANIS participation is followed by a decrease in triglyceride levels. There is no significant correlation between the duration of PROLANIS participation and triglyceride levels in T2DM patients at Griya Sehat Colomadu Clinic. Future research should implement more specific inclusion criteria and control for other confounding factors.